2022
DOI: 10.1098/rstb.2020.0498
|View full text |Cite|
|
Sign up to set email alerts
|

Early to mid-Holocene human activity exerted gradual influences on Amazonian forest vegetation

Abstract: Humans have been present in Amazonia throughout the Holocene, with the earliest archaeological sites dating to 12 000 years ago. The earliest inhabitants began managing landscapes through fire and plant domestication, but the total extent of vegetation modification remains relatively unknown. Here, we compile palaeoecological records from lake sediments containing charcoal and from pollen analyses to understand how human land-use affected vegetation during the early to mid-Holocene, and place our results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 140 publications
0
16
0
1
Order By: Relevance
“…The frequency and abundances of charcoal fragments and phytoliths indicating disturbance across our three study sites were lower than has been reported at other sites in central and eastern Amazonia where similar analyses have been performed on terrestrial soils (McMichael et al, 2012 , 2015 ). Data from lake sediments have also indicated that the frequency of forest opening and burning by people in the pre‐Columbian era was lower in northwestern Amazonia compared with the southwestern and central regions of the basin (Gosling et al, 2021 ; Nascimento et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and abundances of charcoal fragments and phytoliths indicating disturbance across our three study sites were lower than has been reported at other sites in central and eastern Amazonia where similar analyses have been performed on terrestrial soils (McMichael et al, 2012 , 2015 ). Data from lake sediments have also indicated that the frequency of forest opening and burning by people in the pre‐Columbian era was lower in northwestern Amazonia compared with the southwestern and central regions of the basin (Gosling et al, 2021 ; Nascimento et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to have initially taken place along river banks and drier fringes of the lowland and montane forest zone. However, within a few millennia, human occupation pushed deeper into the Amazon forest, primarily along river networks, although archaeological evidence may be biased to such accessible sites [ 19 , 20 ]. Human occupation modes ranged from hunting and gathering to agricultural systems which were based either on locally originated domestications such as manioc and squashes, or imported from Mesoamerica, such as maize.…”
Section: The Tropics: a Frontier For The Deep Human Pastmentioning
confidence: 99%
“…Cultivation dating to 9 ka also appears in the forest zone north of the savannahs [ 91 ], and there are signs of cultivation near campsites in northwest Amazonia [ 80 ]. In regions away from plant cultivation, early- to mid-Holocene foragers consumed palms, tree fruits and nuts [ 20 ]; many of these species are now hyperdominant in Amazonia and it has been suggested that the elevated abundance of these species across Amazonia may reflect selection and stewardship by indigenous populations over millennia [ 84 ].…”
Section: Neotropical Forestsmentioning
confidence: 99%
“…Charcoal fragments are evidence of human activity in the closed canopy forests of Amazonia, as fire rarely spreads from natural ignitions because of the everwet conditions (Bush et al, 2008; Malhi et al, 2009; Uhl & Kauffman, 1990). Although interdisciplinary archaeological and palaeoecological datasets unanimously indicate that fire, cultivation and cultural complexity increase over the last several millennia, these patterns were not uniformly intense across the vastness of Amazonia (Heckenberger & Neves, 2009; McMichael et al, 2012; Nascimento et al, 2022; Oliver, 2008; Piperno, 2011; Riris & Arroyo‐Kalin, 2019).…”
Section: Introductionmentioning
confidence: 99%